Youtube as a source of information about symptomatic irreversible pulpitis: Quality and content analysis - Ocak, Mevlüt Sinan; Yılmaz, Betül (Turkish Endodontic Society, 2025)
Purpose: With the advancement of technology, both patients and healthcare professionals increasingly seek information. However, analysis of the data hosted by various platforms that allow rapid access to such information via the internet remains underexplored. This study aims to evaluate the content accuracy and educational quality of YouTube videos related to symptomatic irreversible pulpitis. Methods: On April 5, 2024, a search was conducted on the YouTube platform using the keyword “Symptomatic irreversible pulpitis.” Initially, 610 videos were screened, but only 32 met the inclusion criteria. The videos were assessed according to five content parameters: Diagnosis, treatment, etiology, prognosis, and symptoms. Quality assessment was conducted using the Video Information and Quality Index (VIQI), which includes information flow, accuracy, technical quality, and title-content consistency. Kruskal-Wallis and Dunn’s tests were used for statistical evaluations. (significance level p<0.05). Results: Among the 32 videos included in the study, 34.4% provided inadequate, 43.8% moderate, and 21.9% high-quality information. Videos providing moderate-quality information had a significantly higher number of likes compared to the other groups (p<0.05). Conclusion: Most YouTube videos related to symptomatic irreversible pulpitis are academically insufficient. There is a growing need for more reliable and higher-quality digital content to be used in dental education. © 2025, Turkish Endodontic Society. All rights reserved.
Keywords: Information; irreversible pulpitis; YouTube